Association between Chinese youth’s sources of sexual knowledge and sexual and reproductive health: a mediation analysis of sexual knowledge level - Xinye Zou; Kefan Xue; Siyu Zou; Angela Y. Xiao; Wenzhen Cao; Kun Tang (Sexual and Reproductive Health Matters)
Changing sexual behaviours among Chinese youth have emerged along with China’s rapid socioeconomic transition. In the context of enduring Confucian traditions and limited formal sexuality education, there is an increasing demand from Chinese youth for accessible and inclusive sexuality education. This research explores how young people in China seek out and engage with sexual knowledge within this shifting cultural landscape. While previous studies indicate that a lack of knowledge in sexual and reproductive health (SRH) is associated with risky sexual behaviours, investigations on how Chinese youth access SRH knowledge and its impact on their behaviours remain unclear. Based on the survey data collected in 2019–20, this cross-sectional study of 52,256 Chinese youth highlighted how young people access and apply sexual knowledge. Boys were more likely to learn from media (primarily pornography), while girls tended to rely on school-based education and parental communication. Mediation analyses were performed to explore the association between sources of sexual knowledge and sexual and reproductive health with a mediator of sexual knowledge scores. The results show that youth who acquired SRH knowledge from the media were more likely to engage in sexual intercourse and experience early sexual debut, while youth gaining SRH knowledge from school were less likely to have sexual intercourse and early debut. Sexual knowledge acquisition occurs not only in one setting but across various settings in young people’s lives. This study provides insights for future sexuality education improvement through different learning sources and emphasises how young people’s learning experiences impact their sexual behaviour.